Brain transcriptomics of nonhuman primates: A review. (14th May 2021) - Pei, Wendi; Fu, Lin; Li, Shui-Qing; Yu, Yang
Highlights: The transcription patterns of brain regions are dynamically reorganized during development and aging. Exposure to alcohol, sevoflurane, valproic acid and methamphetamine induces adverse effects on brain. Potential therapeutic targets for neurological disorders are identified. Targeted therapeutic effects and the spatiality of primate brain transcriptome warrant further investigation. Abstract: The brain is one of the most important and intricate organs in our bodies. Interpreting brain function and illustrating the changes and molecular mechanisms during physiological or pathological processes are essential but sometimes difficult to achieve. In addition to histology, ethology and pharmacology, the development of transcriptomics alleviates this condition by enabling high-throughput observation of the brain at various levels of anatomical specificity. Moreover, because human brain samples are scarce, the brains of nonhuman primates are important alternative models. Here in this review, we summarize the applications of transcriptomics in nonhuman primate brain studies, including investigations of brain development, aging, toxic effects and diseases. Overall, as a powerful tool with developmental potential, transcriptomics has been widely utilized in neuroscience.